Comparative analysis of the temples of Khajuraho and the ruling Chandellas of India - Gill, Chelsea (My University, 2008)
As the Chandella Empire gained control of central India in the 10th century A.D. the Chandella began to build the temples of Khajuraho. An estimated 85 temples once existed, now only 24 remain in Khajuraho today. The still standing temples were all built between A.D. 900 and 1150. By investigating the complexity of the temples architectural style over time, as well as the sculptures on the temples, insights into the growth and decline of the Chandellas reign are found. In addition, the temples contain information about the religions present under the Chandella rule and how the religions diversify as they gained power and influence over the region. The temples suggest a correlation between religious pluralism and architectural complexity as the Chandellas influence develops, however, this does not imply a cause and effect.
Keywords: Religious pluralism -- India; Chandela dynasty; Temples -- India -- Khajuraho